Modernização agrícola e a região da Alta Mogiana Paulista: análise da expansão da produção de cana-de-açúcar em uma tradicional região cafeeira - Carvalho, Thiago Franco Oliveira de [UNESP] (2014)
The present study analyses the implications arising from the sugarcane expansion in the Alta Mogiana region. Despite being former, the sugarcane production in this territory was relatively unexpressive until the 1990s. Thereafter, the acreage increased significantly, intensifying itself particularly over the 2000s due to incentive programs of the government to the ethanol production, and increased global demand for renewable fuels and sugar. Therefore, this region known as ―Coffee Belt‖ since the late nineteenth century, has been suffering a process of simultaneous coexistence and productive restructuring of the coffee plantations and sugarcane, resulting in changes in rural and urban areas. Thereby, the present study investigated the implications of the sugarcane expansion in this region, such as modernization and loss of the agricultural diversity, land concentration, changes in the market and population dynamics. Analysis of the characters of the sugarcane industry productive space circuit and their respective cooperation circles show how these transformations in this region are happening due to productive reconversion of the agricultural space and its interactions with others agricultural activities, especially with the coffee plantations